Osteogenic differentiation of 3D cultured mesenchymal stem cells induced by bioactive peptides - Lukasova, Vera; Buzgo, Matej; Sovkova, Vera; Dankova, Jana; Rampichova, Michala; Amler, Evžen (Cell proliferation, 2017)
OBJECTIVES: Bioactive peptides derived from receptor binding motifs of native proteins are a potent source of bioactive molecules that can induce signalling pathways. These peptides could substitute for osteogenesis promoting supplements. The work presented here compares three kinds of bioactive peptides derived from collagen III, bone morphogenetic protein 7 (BMP-7) and BMP-2 with their potential osteogenic activity on the model of porcine mesenchymal stem cells (pMSCs). MATERIALS AND METHODS: pMSCs were cultured on electrospun polycaprolactone nanofibrous scaffolds with different concentrations of the bioactive peptides without addition of any osteogenic supplement. Analysis of pMSCs cultures included measurement of the metabolic activity and proliferation, immunofluorescence staining and also qPCR. RESULTS: Results showed no detrimental effect of the bioactive peptides to cultured pMSCs. Based on qPCR analysis, the bioactive peptides are specific for osteogenic differentiation with no detectable expression of collagen II. Our results further indicate that peptide derived from BMP-2 protein promoted the expression of mRNA for osteocalcin (OCN) and collagen I significantly compared to control groups and also supported deposition of OCN as observed by immunostaining method. CONCLUSION: The data suggest that bioactive peptide with an amino acid sequence of KIPKASSVPTELSAISTLYL derived from BMP-2 protein was the most potent for triggering osteogenic differentiation of pMSCs.
Keywords: Animals; Swine, Miniature; kolagen typu I; mezenchymální kmenové buňky; osteogeneze; Microscopy, Electron, Scanning; Collagen Type II; buněčná diferenciace; mikroskopie elektronová rastrovací; osteokalcin; miniaturní prasata; prasata; Osteocalcin; kultivované buňky; Mesenchymal Stem Cells; Cells, Cultured; peptidy; Swine; kolagen typ II; Cell Differentiation; buněčné kultury; Osteogenesis; zvířata; Cell Culture Techniques; konfokální mikroskopie; Collagen Type I; Microscopy, Confocal; Peptides